1994
DOI: 10.1111/j.1365-2923.1994.tb02737.x
|View full text |Cite
|
Sign up to set email alerts
|

Young hospital doctors after night duty: their task-specific cognitive status and emotional condition

Abstract: Sleep deprivation is an unpleasant burden of young hospital doctors during their medical training. It may disrupt the balance between coping strategies available to them and the professional demands encountered. Impaired medical care offered by sleep-deprived juniors may be a consequence. Valid research work on this subject is rare and surprisingly contradictory. Therefore, we evaluated the task-specific cognitive status and emotional condition of 40 young hospital doctors (27 men and 13 women, 29.9 +/- 2.9 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
5

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 23 publications
1
53
0
5
Order By: Relevance
“…Hodiamont et al 25) showed a higher mean GHQ score among divorced people than for any other marital status. The reason for this association has not been fully understood; however, several hypotheses have been proposed.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Hodiamont et al 25) showed a higher mean GHQ score among divorced people than for any other marital status. The reason for this association has not been fully understood; however, several hypotheses have been proposed.…”
Section: Discussionmentioning
confidence: 94%
“…This study showed night duty to be a significant factor associated with psychological distress, even when adjusting for other factors, including working time. Other studies have shown that night work is a critical occupational stressor 24) , and that night duty for doctors has more impact on physical and mental health because of sleep deprivation and psychological pressure 25) . Furthermore, for female doctors, night duty may be an obstacle to their household duties.…”
Section: Discussionmentioning
confidence: 99%
“…The task was completion of a complex numeric pattern. Lingenfelser et al (1994) compared the performance of 40 young doctors after a night off (at least 6 hours sleep) and after a night on call (in the hospital for 24 hours). Tasks were connecting numbers, recall of a list of items, choice reaction time, Stroop test, and electrocardiogram simulation.…”
Section: Medicinementioning
confidence: 99%
“…Older subjects have been shown to be more affected by sleep deprivation in comparison to younger subjects (Lingenfelser et al, 1994;. Most studies seem to have more male than female participants (Thomas et al, 2000).…”
Section: Subject Variabilitymentioning
confidence: 99%